INOVASI PELAYANAN PUBLIK DI BADAN PENANAMAN MODAL DAN PELAYANAN TERPADU (BPMPT) KABUPATEN KUBU RAYA (PUBLIC SERVICES INNOVATION IN REGIONAL BOARD OF INVESTMENT AND INTEGRATED SERVICES (BPMPT) AT KUBU RAYA REGENCY) - Maria Agustini Permata Sari (Pusjar SKPP Lembaga Administrasi Negara, 2014)
As a relatively new area, Kubu Raya district has managed to implement good public services especially in the field of licensing, this is evidenced by the numerous awards achieved and the increasing trend of the realization of a permit issued by the permitting Regional Board Of Investment And Integrated Services (BPMPT) as organizers each year. This study aims to determine what innovations have been carried out by BPMPT Kubu Raya and to identify what factors into supporting or occurrence of such innovations. This study used a qualitative method with a descriptive approach . Data were collected through interviews with the Head BPMPT and secondary data. The success of the public service is a direct and indirect impact of the innovation made by BPMPT. Innovation has been done by BPMPT Kubu Raya is simplifying the number of permits, licenses and restrictions touts business process simplification. Factors driving the birth of innovation undertaken by BPMPT Kubu Raya is the commitment and leadership of Regents BPMPT in improving the quality of licensing services, and human resources BPMT, who has high morale. While the issue is a barrier in the birth of innovation is movingstaff.Keywords: Innovation, Public ServicesSebagai daerah yang masih terhitung baru, Kabupaten Kubu Raya sudah berhasil melaksanakan pelayanan publik yang baik khususnya di bidang perijinan, hal ini dibuktikan antara lain dengan diraihnya berbagai penghargaan dan meningkatnya tren realisasi ijin yang diterbitkan oleh Badan Penanaman Modal dan Pelayanan Terpadu (BPMPT) setiap tahunnya. Studi ini bertujuan untuk mengetahui inovasi apa saja yang sudah dilakukan oleh BPMPT Kabupaten Kubu Raya serta untuk mengidentifikasi faktor apa saja yang menjadi pendorong maupun penghambat terjadinya inovasi tersebut. Studi ini menggunakan metode kualitatif dengan pendekatan deskriptif. Data dikumpulkan melalui wawancara dengan Kepala BPMPT serta data sekunder. Hasil studi ini menyimpulkan bahwa inovasi yang sudah dilakukan oleh BPMPT Kubu Raya adalah penyederhanaan jumlah ijin, pembatasan calo perijinan dan penyederhanaan business process. Faktor pendorong lahirnya inovasi yang dilakukan oleh BPMPT Kubu Raya adalah komitmen Bupati dan pimpinan BPMPT dalam memperbaiki kualitas pelayanan perijinan, serta sumber daya manusia BPMT yang memiliki semangat kerja tinggi. Sedangkan masalah yang menjadi faktor penghambat lahirnya inovasi adalah mutasipegawai.Kata Kunci: Inovasi, Pelayanan Publik